In Situ Atomic‐Scale Observation of Monolayer MoS2 Devices under High‐Voltage Biasing via Transmission Electron Microscopy - Tseng, Yi‐Tang; Lu, Li‐Syuan; Shen, Fang‐Chun; Wang, Che‐Hung; Sung, Hsin‐Ya; Chang, Wen‐Hao; Wu, Wen‐Wei (Small (Weinheim an der Bergstrasse, Germany), 2022)
2D materials have great potential for not only device scaling but also various applications. To prompt the development of 2D electronics and optoelectronics, a better understanding of the limitation of materials is essential. Material failure caused by bias can lead to variations in device behavior and even electrical breakdown. In this study, the structural evolution of monolayer MoS2 with high bias is revealed via in situ transmission electron microscopy at the atomic scale. The biasing process is recorded and studied with the aid of aberration‐corrected scanning transmission electron microscopy. The effects of electron beam irradiation and biasing are also discussed through the combination of experiments and theory. It is found that the Mo nanoclusters result from disintegration of MoS2 and sulfur depletion, which are induced by Joule heating. The thermal stress can also damage the MoS2 layer and form long cracks in both in situ and ex situ biasing cases. Investigation of the results obtained with different applied voltages helps to further verify the mechanism of evolution and provide a comprehensive study of the function of biasing. The high‐voltage biasing of monolayer MoS2 devices is demonstrated through in situ TEM and aberration‐corrected STEM to explore the mechanism of the material failure. During in situ TEM biasing, the MoS2 device is damaged by knock‐on damage, and the atomic migration induced by Joule heating. Also, long cracks formed by thermal stress are discussed in this research.